Adaptasi antarbudaya di kalangan satuan Nindya Praja Institut Pemerintahan Dalam Negeri (IPDN) di Jatinangor - Choirunnisa, Farida Anggun; Aprianti, Agus (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
The interactions that occur between one another cannot be separated from life, because human life is a social creature that requires interaction with another. In the interactions that occur, there must be cultural differences between one another, because of these cultural differences, the process of intercultural adaptation. One of them happened at the Institute of Domestic Government (IPDN). IPDN itself has students from 34 provinces in Indonesia and has different ethnicities from one another so that in carrying out education at IPDN, the IPDN Praja undertakes an intercultural adaptation process to eliminate the gaps that occur, making it easier for them to communicate. The focus of this research is to provide an overview of the intercultural adaptation taking place between the IPDN Nindya Praja Units in Jatinangor, as well as to identify the intercultural communication between the IPDN Nindya Praja Units in Jatinangor. The research method used in this research is a qualitative method with a phenomenological. The data obtained through in-depth interviews, observation, and literature study using a variety of literature which is the source of the research. The results obtained indicate that Nindya Praja IPDN has experienced an intercultural adaptation process that differs from another, in differences of language and speech style. Besides, environmental factors and communication factors also influence the intercultural adaptation process of Nindya Praja IPDN.Â